Characterisation of waste water from biomass gasification equipment: a case-study from Cambodia. (2015) - Shackley, Simon
The gasification of rice husks for small-scale power generation in rice mills and other small factories in Cambodia has spread rapidly in the past decade and has a favourable investment payback period where the facility is off-grid. The technology is widely regarded as a sustainable, low-carbon power option. However, installed gasification technologies produce a black waste water which is frequently disposed of into the local environment without any treatment. An analysis was undertaken to identify and measure the key potential contaminants and compare concentrations in the water and sediment with regulatory thresholds established in Cambodia and within other jurisdictions. It was found that concentrations of organic contaminants such as phenols and benzene-type molecules (BETX) (water and sediment) and polycyclic aromatic hydrocarbons (PAHs) (sediment), as well as macro water quality indicators, were far higher than regulatory thresholds prescribe, posing threats to sensitive aquatic ecosystems into which such waste is introduced.